Impacto socioeconómico de la operatividad del sistema Carrizal Chone I en el Cantón Bolívar periodo 2007 - 2010 - García Zambrano, María José (2012)
The Open Trade process in Ecuador has significant influence on the rural sector, given limited conditions to compete with the new market requirements, restricting the ability of businesses and threatening the reduction of food for domestic consumption; the Project Carrizal Chone 1 was created in order to increase crop and livestock production in the north-central of Manabí and improve the quality of life for the families. This research is based on the performance of a social economical study of 30 communities in the area of influence of the Carrizal system in the Bolivar Canton reflecting current data using a triangulation of the reality leading to statistical techniques such as survey, interview and guided observation that once represented statistically it was able to determined the social migratory movement, levels of education by the owners and their children, identify which the agricultural and livestock production were more relevant, it also shows how the project has influenced in their income, comparing the economic situation among those using the system and those without it. Achieving all this will determine the quality of life for families within the project from the environmental, basic services and housing point of view.